1997
DOI: 10.2166/wst.1997.0179
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of metal removal by a laboratory scale wetland

Abstract: This paper presents a preliminary assessment of the heavy metal removal performance by a laboratory scale wetland based on the design of a constructed wetland treating surface runoff. Laboratory scale gravel-substrate subsurface-flow wetlands in a continuous recirculating mode were studied regarding the removal of Cu, Pb and Zn from contaminated water. After establishing the flow characteristics, the wetland was planted with Typha latifolia, Phragmites australis, Schoenoplectus lacustris and Iris pseudacorus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…Moreover, the uptake of all metals by Scirpus littoralis is stronger in the BO than in the shoots of this plant as shown by the mean B/S, T/S, T/B and B/W ratios. This agrees with several studies indicating that more accumulation occurs in the BO than in the shoots of the wetland plants (Mudroch, 1979;Welsh et al, 1980;Taylor et al, 1983;Babcock et al 1983;Jain et al, 1990;Sen et al, 1989;Kadelec, 1995;Mungur et al, 1997;Zayed et al, 1998;Qian et al, 1999;Sadwosky 1999;Mehra et al, 1998;Cordes et al, 2000, Mehra andZurayk 2002).…”
Section: Metal Content In Soil and Watersupporting
confidence: 91%
“…Moreover, the uptake of all metals by Scirpus littoralis is stronger in the BO than in the shoots of this plant as shown by the mean B/S, T/S, T/B and B/W ratios. This agrees with several studies indicating that more accumulation occurs in the BO than in the shoots of the wetland plants (Mudroch, 1979;Welsh et al, 1980;Taylor et al, 1983;Babcock et al 1983;Jain et al, 1990;Sen et al, 1989;Kadelec, 1995;Mungur et al, 1997;Zayed et al, 1998;Qian et al, 1999;Sadwosky 1999;Mehra et al, 1998;Cordes et al, 2000, Mehra andZurayk 2002).…”
Section: Metal Content In Soil and Watersupporting
confidence: 91%
“…Copper nitrate and nickel nitrate were added to the inflow water of Filter 2 and Filters 7 to 12 to give total concentrations of dissolved copper and nickel of approximately 1 mg/L for each metal, comparable to figures reported for urban water heavily contaminated with heavy metals and mine wastewater (Cooper et al, 1996;Kadlec and Knight, 1996;Mungur et al, 1997;Scholz and Xu, 2002).…”
Section: Metal Nitratessupporting
confidence: 56%
“…(common reed). They are used to treat storm runoff, domestic and industrial wastewater (Cooper et al, 1996;Kadlec and Knight, 1996;Scholz, 2003), and have also been applied for passive treatment of mine wastewater drainage (Mungur et al, 1997;Mays and Edwards, 2001). …”
Section: Introduction Cmentioning
confidence: 99%
“…There are several studies with wetland microcosms that investigated nutrient removal (Rogers et al, 1991, Drizo et al, 1997. Heavy metal removal experimentation was also established and researchers demonstrated that macrophytes, such as Typha latifolia, Phragmites australis, Schoenoplectus lacustris, and Iris pseudacorus, can be used for heavy metal removal (Mungur et al, 1997).…”
Section: Introductionmentioning
confidence: 99%